Automation and flexible labor contracts: Firm-level evidence from Italy - Silvio Traverso; Massimiliano Vatiero; Enrico Zaninotto (Global Labor Organization (GLO), 2024)
This study examines the association between investments in automation technologies and employment outcomes at the firm level, utilizing a panel dataset of about 10,450 Italian firms. Focusing on the proliferation of non-standard, flexible labor contracts introduced by labor market reforms in the 2000s, we identify a positive relationship between automation investments and the adoption of flexible labor arrangements. With the aid of a conceptual framework, we interpret these findings as evidence of complementarity between flexible capital, represented by automation technologies, and flexible labor, manifested through non-standard contractual arrangements. This complementarity is crucial for enhancing operational flexibility, a critical determinant of firm performance in the modern market environment. However, while this adaptability is beneficial for firms, it raises concerns about job security, the potential for lower wages among workers, and the reduction of workers' incentives to invest in human capital. In terms of policy implications, our analysis underscores the need for measures that safeguard workers' interests without compromising the efficiency gains from automation.
Keywords: D20; J30; J41; K31; 330; Automation; Labor Contracts; Flexible Capital; Flexible Labor